Quantum characterization of materials using the density functional theory - Uribe-Suárez, Carlos Alberto; Hernández-Ramos, Ricardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
Theoretical characterization of materials, from quantum mechanics, reveals entirely novel aspects. Its implementation requires prior knowledge of its crystalline structure, the atoms that compose it and their positions in it (First Principles). Solving the Schrodinger's equation is possible to know the energy ofthe crystalline system and with it the value of the parameter of the network that minimizes it. With these are determined the values of energy in different directions of first Brillouin zone or band structure, finally this information leads to the mechanical, electrical and optical characterization of material